Use of rotary kilns for solar thermal applications: Review of developed studies and analysis of their potential. (1st March 2017) - Alonso, E.; Gallo, A.; Roldán, M.I.; Pérez-Rábago, C.A.; Fuentealba, E.
Highlights: Solar rotary kilns have been reviewed and compared to classical rotary kilns. Models and experimental prototypes of solar rotary kilns have been analysed. Rotary movement favours the radiation heat transfer. There are limitations that restrict the development of solar rotary kilns. Knowledge on classical industry should be applied for solar technology development. Abstract: Rotary kilns have a long history of use in classical industries. They are able to achieve high temperatures with higher thermal efficiencies than other reactor types. Their performance has been widely studied and classified according to different parameters. Since it is a well-known technology, rotary kilns have been selected for high temperature solar processes. This article initially presents a brief review of the rotary kiln technology and it focuses on the employment of these devices for thermal and thermochemical processes conducted by concentrating solar energy. Among the solar devices, a novel rotary kiln prototype for thermochemical processes is presented and compared with a static solar reactor. Finally, some practical conclusions on the design and operation of solar rotary kilns are remarked and an analysis of their main limitations is presented.